Бесконтактный синхронный генератор с самовозбуждением - Усачев С. П. Cергей Прокопьевич; Юнда Н. И. Николай Иванович; Попов В. И. Виталий Иванович; Хорьков К. А. Константин Александрович; Сипайлов Г. А. Геннадий Антонович
опубл. 15.10.90